Exploring the Determinants that Control Information Overload and Postgraduate Research Performance: Conceptual Model and Implications for Future Research - Hasan Al-Kumaim, Nabil; Hasnah Hassan, Siti; Imran Qureshi, Muhammad; Mahmood, Arshad; Khan, Nohman (International Journal of Psychosocial Rehabilitation, 2020)
This study was performed in one of the top five research universities in Malaysia to explore the impact of information overload (IO) on academic research performance among postgraduate students. It aims to get a deep understanding of the (IO) phenomenon effect on postgraduate research performance, and what are the possible determinants could control this effect. In-depth semi-structured individual interviews and one focus group interview were employed. Purposive and snowballing sampling has been implemented for data collection and verification. Numerous studies in many fields of sciences have been conducted about the aggravated effect of IO phenomenon and its impacts on the social, personal and organizational level. However, inadequate studies found to address the problem of information overload among postgraduate academic researchers. Most of the participants in this study exposed that IO represents a real miserable problem that severely affects their research performance in different stages of their research. Two main contributions introduced in this phenomenological research. First, this study proposed an original conceptual model, which includes four possible moderators identified as (a) information literacy, (b) self-efficacy, (c) expert’s consultation, (d) supervisor support. These factors could play a role to control information overload and its effect on postgraduate students’ research performance. The research’s conceptual model was shaped based on synthesized perceptions extracted from data was collected and supported by relevant literature. Five of highly academician experts in the field assessed the conceptual model. Second, several practical insights and recommendations were provided to the decision makers and specialists in higher education institutions and academic filed on how to manage information overload and reduce its negative effects among postgraduate students.